2011
DOI: 10.5194/astra-7-507-2011
|View full text |Cite
|
Sign up to set email alerts
|

EAS hadronic component as registered by a neutron monitor

Abstract: For the purposes of a study of hadron component of an extended air shower (EAS), two detectors of cosmic rays (CR) were joined at the Baksan Neutrino Observatory. They are an EAS array detector (the "Carpet") and a neutron monitor (NM). Due to the versatility of a new recording system a master-pulse, which comes from the "Carpet" and marks to occurring of EAS, is joined to NM data. After processing of the huge data set it is found that the time of EAS influence on NM is less than 1 ms. The distribution of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…According to the developers of the neutron monitor data recording system from the Polar Geophysical Institute, the outliers are of physical origin and are caused by the arrival of ultrahigh-energy particles that produce multiple stars in the body of the monitor. Special studies of this phenomenon are being pursued [Balabin et al, 2011;Balabin et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
“…According to the developers of the neutron monitor data recording system from the Polar Geophysical Institute, the outliers are of physical origin and are caused by the arrival of ultrahigh-energy particles that produce multiple stars in the body of the monitor. Special studies of this phenomenon are being pursued [Balabin et al, 2011;Balabin et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of delayed low-energy hadrons after the arrival of a cosmic-ray Extended Air Shower (EAS) can be an effective probe to determine whether an EAS is hadronic in origin. Neutrons have been found to arrive up to a millisecond after the detection of the core electromagnetic component of an EAS [1]. Simulation studies have reported that the delay is largely dependent on the neutron energy, with a flux of much lower energy thermalised neutrons arriving many milliseconds after the initial EAS [2].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of delayed low-energy hadrons after the arrival of a cosmic-ray Extended Air Shower (EAS) can be an effective probe to determine whether an EAS is hadronic in origin. Neutrons have been found to arrive up to a millisecond after the detection of the core electromagnetic component of an EAS [1]. Simulation studies have reported that the delay is largely dependent on the neutron energy, with a flux of much lower energy thermalised neutrons arriving many milliseconds after the initial EAS [2].…”
Section: Introductionmentioning
confidence: 99%